Galápagos mockingbirds tolerate introduced parasites that affect Darwin's finches. Issue 4 (April 2016) - Knutie, Sarah A.; Owen, Jeb P.; McNew, Sabrina M.; Bartlow, Andrew W.; Arriero, Elena; Herman, Jordan M.; DiBlasi, Emily; Thompson, Michael; Koop, Jennifer A. H.; Clayton, Dale H.
Abstract: Introduced parasites threaten native host species that lack effective defenses. Such parasites increase the risk of extinction, particularly in small host populations like those on islands. If some host species are tolerant to introduced parasites, this could amplify the risk of the parasite to vulnerable host species. Recently, the introduced parasitic nest fly Philornis downsi has been implicated in the decline of Darwin's finch populations in the Galápagos Islands. In some years, 100% of finch nests fail due to P. downsi ; however, other common host species nesting near Darwin's finches, such as the endemic Galápagos mockingbird ( Mimus parvulus ), appear to be less affected by P. downsi . We compared effects of P. downsi on mockingbirds and medium ground finches ( Geospiza fortis ) on Santa Cruz Island in the Galápagos. We experimentally manipulated the abundance of P. downsi in nests of mockingbirds and finches to measure the direct effect of the parasite on the reproductive success of each species of host. We also compared immunological and behavioral responses by each species of host to the fly. Although nests of the two host species had similar parasite densities, flies decreased the fitness of finches but not mockingbirds. Neither host species had a significant antibody‐mediated immune response to P. downsi . Moreover, finches showed no significant increase in begging, parental provisioning, or plasma glucose levels in response to the flies. In contrast, parasitized mockingbird nestlings begged more than nonparasitized mockingbird nestlings. Greater begging was correlated with increased parental provisioning behavior, which appeared to compensate for parasite damage. The results of our study suggest that finches are negatively affected by P. downsi because they do not have such behavioral mechanisms for energy compensation. In contrast, mockingbirds are capable of compensation, making them tolerant hosts, and a possible indirect threat to Darwin's finches.